2017
DOI: 10.1155/2017/9876076
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Sensitivity Analysis of Quasi-Scholte Wave Liquid Sensing by Analytical Methods

Abstract: Ultrasonic-guided wave sensing relies on perturbation of wave propagation by changing physical properties of the target media. Solid waveguides, through which guided waves can be transduced between the transducer and the target media, are frequently employed for liquid sensing and several other applications. In this manuscript, liquid sensing sensitivity of dispersive quasi-Scholte waves, which are guided interface waves that travel at the solid-liquid boundary, is investigated. Dispersion analysis of quasi-Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many studies have investigated how the Scholte velocity changes with the ratio of the densities, with the bulk speeds of sound, and with the Rayleigh velocity, which itself depends on the bulk speeds of sound in the solid [8,21,22,25]. Others adopted a simplified view that a soft interface is one where the transverse speed of sound in the solid is less than the speed of sound in the fluid (c T < c F ), with interfaces not meeting this criteria being hard [3][4][5].…”
Section: The Scholte Modementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated how the Scholte velocity changes with the ratio of the densities, with the bulk speeds of sound, and with the Rayleigh velocity, which itself depends on the bulk speeds of sound in the solid [8,21,22,25]. Others adopted a simplified view that a soft interface is one where the transverse speed of sound in the solid is less than the speed of sound in the fluid (c T < c F ), with interfaces not meeting this criteria being hard [3][4][5].…”
Section: The Scholte Modementioning
confidence: 99%
“…For a hard plate, the symmetric coupled Scholte mode or S mode, whose displacement amplitude is symmetric about the center of the plate, appears to be nondispersive, with a phase velocity approximately equal to that of the surrounding fluid [17,18]. As a result, many studies neglect its existence, reporting only a single antisymmetric coupled Scholte mode, referred to as the quasi-Scholte mode or A mode [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Q-Sch waves can be used to characterize the fluid properties [87] since the wave attenuation, phase and group velocity are affected by the viscosity, longitudinal bulk attenuation and bulk velocity of the fluid. In [88] the influence of the waveguide material (steel, aluminium and brass) on the Q-Sch mode phase and group velocity sensitivities to the liquid parameters (longitudinal velocity and density) is theoretically studied. The study concluded that higher waveguide material density leads to higher sensitivities, and higher waveguide acoustic velocities lead to an extended effective sensing range.…”
Section: Fundamental Anti-symmetric Modementioning
confidence: 99%
“…Q-Sch waves can be used to characterize the fluid properties[90] since the wave attenuation, phase and group velocity are affected by the viscosity, longitudinal bulk attenuation and bulk velocity of the fluid. In reference[91] the influence of the waveguide material (steel, aluminium and brass) on the Q-Sch mode phase and group velocity sensitivities to the liquid parameters (longitudinal velocity and density) is theoretically studied. The study concluded that higher waveguide material density leads to higher sensitivities, and higher waveguide acoustic velocities lead to an extended effective sensing range.As an example figure 5.2.3 shows Scholte mode phase and group velocity dispersion curves in Al plate (1 mm thick) immersed in water (ρ = 1000 kg/m 3 , v =1500 m/s), benzene (ρ = 881 kg/m 3 , v = 1117 m/s, dynamic viscosity η = 0.65·10-3 Ns/m 2 ) and diesel (ρ = 800 kg/m 3 , v =1250 m/s ).…”
mentioning
confidence: 99%